Some Biochemical Aspects Of Tyrosine Aminotransferase (L-Tyrosine: 2-Oxoglutarate Aminotransferase, E.C. 2.6.1.5) (TAT) In The Stages Of Development Of Aedes Aegypti Linnaeu - Chan, Guat Lian (1976)
The variation of tyrosine-2-oxoglutarate amino-transferase (EC.2.6.1.5), TAT and soluble protein was charted throughout the postembryonic development and young adult growth of the mosquito, Aedes aegypti (Linnaeus). A close correspondence between the enzyme activity and soluble protein content was observed during the immature stages of development. Peak transaminase activity was encountered in· the middle fourth larval instar followed by a decline in activity prior to pupation. At its maximum activity, the insect enzyme compared well with the adult rat liver enzyme in activity. The larval enzyme appeared to exhibit a diurnal rhythm of activity characterized by a steady increase in activity from 0600 hours to reach maximum activity at 24 hours.